An Optimized Multilevel Inverter Topology with Symmetrical and Asymmetrical DC Sources for Sustainable Energy Applications - Manjunatha, B. M.; Nagaraja Rao, S.; Suresh Kumar, A.; Shaguftha Zabeen, K.; Lakshminarayanan, S.; Reddy, A. V. (Engineering, Technology & Applied Science Research, 2020)
This paper proposes an optimized Multi-Level Inverter (MLI) topology with symmetrical and asymmetrical DC sources for sustainable energy applications. The proposed MLI has optimized components to reduce size, cost, and installation area in comparison with traditional MLIs. It also improves output power quality by reducing harmonics in the stepped output, and hence it can be used for sustainable energy applications with a grid interface. The proposed inverter is equipped with six switching devices, one clamping diode, and two DC sources. It produces a five-level stepped output when using symmetrical DC sources and a seven-level stepped output when using asymmetrical DC sources. In this topology, the six switching devices are divided into two units, namely the level generator and the polarity generator units, the switches used in the level generator are responsible for producing the required number of levels in the form of rectified stepped output and the switches used in the polarity generator are responsible for converting the rectified stepped waveform to stepped AC output. The simulation results verify the operation of the MLI when fed with linear load with symmetrical and asymmetrical DC sources, and the experimental output results are presented for validation.